Experience with ospemifene in patients with vulvovaginal atrophy treated with laser therapy: case studies - Félix Lugo Salcedo; Zuramis Estrada Blanco (BioExcel Publishing Ltd, 2020)
Vaginal laser therapy is a non-hormonal treatment option for vulvovaginal atrophy (VVA), a component of the genitourinary syndrome of menopause. Through a microablative and/ or thermal effect on atrophic vaginal epithelium, laser therapy activates growth factors that increase vascularity and collagen production. Laser and ospemifene are complementary treatments: the laser's effects on intra- and extracellular water are supported by the activity of ospemifene at estrogen receptors to restore vaginal epithelium and natural lubrication. This article reports the clinical course of two women with dyspareunia preventing sexual intercourse who were treated with ospemifene and laser therapy. The woman in case 1 had extreme vaginal stenosis and severe VVA symptoms. CO2 laser therapy accompanied by estriol vaginal gel and vaginal moisturizer was unsuccessful. After ospemifene and three sessions of laser therapy, followed by vaginal ring resection and continued physiotherapy-directed mechanical dilation of the vagina, she was asymptomatic within 6 months. The woman in case 2 had severe VVA, which had prevented penetration for 2 years. Ospemifene was administered for 1 month to prepare the vaginal epithelium for photothermal therapy. A single erbium:YAG laser session and continued ospemifene treatment improved her symptoms sufficiently to allow her to resume sexual relations within 2 months.